Reservation wages of first and second generation migrants - Amelie F. Constant; Annabelle Krause; Ulf Rinne; Klaus F. Zimmermann (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
This paper analyzes the reservation wages of first and second generation migrants. Based on recently collected and rich survey data of a representative inflow sample into unemployment in Germany, we empirically test the hypothesis that reservation wages increase from first to second generation migrants. Two extensions of the basic job search model, namely an unknown wage offer distribution and different reference standards, provide theoretical justifications for this conjecture. In both extensions, changing frames of reference are identified as a channel through which the phenomenon of increasing reservation wages may arise. In as far as language skills or self-evaluated returns to characteristics reflect a person's frames of reference, we find empirical support for this mechanism to be present.
Keywords: F22; J15; J61; J64; 330; Migration; Ethnic Identity; Ethnosizer; Germany; Unemployment; Job Search; Reservation Wages